Antimicrobial Resistance and Virulence-Associated Markers in Campylobacter Strains From Diarrheic and Non-diarrheic Humans in Poland - Wysok, Beata; Wojtacka, Joanna; Hänninen, Marja-Liisa; Kivistö, Rauni (Frontiers in Microbiology, 2020)
Campylobacteriosis is one of the most common causes of bacterial gastroenteritis. However, the clinical course of the illness varies in symptoms and severity. The aim of this study was to characterize Campylobacter jejuni (34 isolates) and C. coli (9 isolates) from persons with diarrheal and non-diarrheal stools at the time of examination and fecal sampling, in Poland by using whole-genome sequencing (WGS). Multilocus sequence typing (MLST) analysis revealed a high diversity with a total of 20 sequence types (STs) among 26 Campylobacter isolates from diarrheic and 13 STs among 17 isolates from non-diarrheic persons. ST-50 and ST-257 were most common in both groups. The phenotypic resistance rate was 74.4% for ciprofloxacin, 67.4% for sulfamethoxazole/trimethoprim, 58.1% for amoxicillin, 48.8% for tetracycline, and 46.5% for ceftriaxone. Only single isolates were resistant to erythromycin, gentamicin, and amoxicillin/clavulanic acid. Overall genotypic resistance toward amoxicillin, fluoroquinolones, tetracyclines, and aminoglycosides was predicted to occur in 93.1, 67.4, 48.8, and 11.6% of the isolates, respectively. None of the isolates showed the presence of the erm(B) gene or mutation in 23S rRNA. Neither was variation found in the important target region in L4 and L22 ribosomal proteins. In regard to the CmeABC efflux pump, a set of variable mutations affecting the regulatory region was noted. All Campylobacter isolates possessed genes associated with adhesion (cadF, jlpA, porA, and pebA) and invasion (ciaB, pldA, and flaC). The type IV secretion system (T4SS) was found in isolates from both diarrheic (15.4%, CI 95%: 6.1–33.5%) and non-diarrheic (23.5%, CI 95%: 9.6–47.3%) persons. The rates of the presence of cytolethal distending toxin cdtABC gene cluster and type VI secretion system (T6SS) were higher in Campylobacter isolates obtained from persons with diarrhea (96.2%, CI 95%: 81.7–99.3% and 26.9%, CI 95%: 13.7–46.1%) compared to isolates from non-diarrheic persons (76.5%, CI 95%: 52.7–90.4% and 11.8%, CI 95%: 3.3–34.3%). The lack of statistically significant differences between two groups in tested virulence factors suggests that individual susceptibility of the host might play more determining role in the disease outcome than characteristics of the infecting strain.